Neurophysiological aspects of musical auditory stimulation on the cardiovascular system - Ferreira, Lucas Lima; Vanderlei, Luiz Carlos Marques; Abreu, Luiz Carlos de; Guida, Heraldo Lorena; Valenti, Vitor Engrácia (ABCS Health Sciences, 2013)
Introduction: The literature has shown that musical stimulation can influence the cardiovascular system, however, the neurophysiological aspects of this influence are not yet fully elucidated. Objective: This study describes the influence of music on the neurophysiological mechanisms in the human body, specifically the variable blood pressure, as well as the neural mechanisms of music processing. Methods: Searches were conducted in Medline, PEDro, Lilacs and SciELO using the intersection of the keyword “music” with the keyword descriptors “blood pressure” and “neurophysiology”. Results: There were selected 11 articles, which indicated that music interferes in some aspects of physiological variables. Conclusion: Studies have indicated that music interferes on the control of blood pressure, heart and respiratory rate, through possible involvement of limbic brain areas which modulate hypothalamic-pituitary functions. Further studies are needed in order to identify the mechanisms by which this influence occurs.